APLIKASI PENCARIAN BENGKEL VESPA DI KOTA DEPOK BERBASIS ANDROID DENGAN METODE LOCATION-BASED SERVICE (LBS) - Dwi Ihtiar; Ryan Rakryan WP; NM Faizah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2022)
The Vespa workshop is the place to organize Vespa repair efforts. Not all Vespa workshop locations are known by the public, both those from Depok City and those from outside the city. This is due to the lack of information about Vespa workshops in Depok City. The progress and development of the times like today's use of technology is needed to be able to provide information quickly, where the use of technology can be accessed anytime and wherever the user is. The use of information technology, such as using an Android-based smartphone application, can be used to help members of the public find a location and find out the route to the desired Vespa workshop. This study aims to build an Android-based Vespa workshop search application as a source of information to find out the location and routes to available locations in Depok City. The research method used is the waterfall process model. Implementation of the Vespa Workshop Application using Javascript programming with Android Studio, Location-based service, and maps sourced from the Google Maps API. The results of the research are in the form of an android-based Vespa workshop search application that helps make it easier for residents of Depok City and outside the region to obtain information about Vespa workshops and routes from the user's location to the desired Vespa workshop in Depok City with the help of GPS.